Leadership through the lens interrogating production, presentation, and power - Murray, Creshema R. (Lexington Books, 2018)
This edited collection looks at leadership on television to investigate issues of race, gender, class, identity, and voice in a variety of workplace and social settings. It examines the constructive and destructive manner in which concepts of leadership are produced to instruct viewers to reflect on their own relationship with leadership.